2019
DOI: 10.1021/acs.analchem.9b00377
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptide Nanofiber Platform for Aβ-Sialic Acid Interaction Analysis and Highly Sensitive Detection of Aβ

Abstract: The variation of amyloid β peptide (Aβ) concentration and Aβ aggregation are closely associated with the etiology of Alzheimer’s diseases (AD). The interaction of Aβ with the monosialoganglioside-rich neuronal cell membrane has been suggested to influence Aβ aggregation. Therefore, studies on the mechanism of Aβ and sialic acids (SA) interaction would greatly contribute to better understanding the pathogenesis of AD. Herein, we report a novel approach for Aβ–SA interaction analysis and highly sensitive Aβ dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…It has been speculated that the reason for the failure of early drug intervention on AD is probably that intervention in the phase is not early enough, which in turn is greatly related to the e cient capture of biological manifestations rather than clinical manifestations in the early diagnosis 47,48 . The experimental results obtained with AIE-CNPy-AD is of great signi cance because APP/PS1 transgenic mice are found to exhibit memory de cits from 5 months old on which is early clinical presentations, con rming that AIE-CNPy-AD can diagnose AD of APP/PS1 transgenic mice during the period of early biological manifestations, prior to the appearance of clinical presentations 43,47,49 . Furthermore, as shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
“…It has been speculated that the reason for the failure of early drug intervention on AD is probably that intervention in the phase is not early enough, which in turn is greatly related to the e cient capture of biological manifestations rather than clinical manifestations in the early diagnosis 47,48 . The experimental results obtained with AIE-CNPy-AD is of great signi cance because APP/PS1 transgenic mice are found to exhibit memory de cits from 5 months old on which is early clinical presentations, con rming that AIE-CNPy-AD can diagnose AD of APP/PS1 transgenic mice during the period of early biological manifestations, prior to the appearance of clinical presentations 43,47,49 . Furthermore, as shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
“…4748 The experimental results obtained with AIE-CNPy-AD is of great significance because APP/PS1 transgenic mice are found to exhibit memory deficits from 5 months old on which is early clinical presentations, confirming that AIE-CNPy-AD can diagnose AD of APP/PS1 transgenic mice during the period of early biological manifestations, prior to the appearance of clinical presentations. 43,47,49 Furthermore, as shown in Figure S15, ThS could neither give discriminatory signals between the APP/PS1 transgenic mice and wild-type mice nor provide distinct signals among mice of different ages, manifesting that our probe outperforms the clinically used gold-standard probe and could be used as an upgraded alternative to the commercially available ones.…”
Section: In-vivo Tracking Of Aβ Plaques In App/ps1 Mice At a Super-eamentioning
confidence: 94%
“…4748 The experimental results obtained with AIE-CNPy-AD is of great significance because APP/PS1 transgenic mice are found to exhibit memory deficits from 5 months old on which is early clinical presentations, confirming that AIE-CNPy-AD can diagnose AD of APP/PS1 transgenic mice during the period of early biological manifestations, prior to the appearance of clinical presentations. 43,47,49 Furthermore, as shown in Figure S15 Figure 6A, 6F, and Figure S16, the Aβ plaques were imaged with high resolution and high contrast. Moreover, it can be clearly observed that the Aβ plaques in brain slices of 6-month-old APP/PS1 transgenic mice were larger and richer in number than those of 4-month-old APP/PS1 transgenic mic, while no significant Aβ plaques were found in the brain slices of 2-month-old, 3-month-old APP/PS1 transgenic mice ( Figure S16), and all the age-matched WT mice ( Figure S17).…”
Section: In-vivo Tracking Of Aβ Plaques In App/ps1 Mice At a Super-eamentioning
confidence: 97%